PENGEMBANGAN BAHAN AJAR KIMIA DASAR BERBASIS CONCEPTUAL CHANGE TEXT PADA MATERI REDOKS - Wati Sukmawati; Asep Kadarohman; Omay Sumarna; Wahyu Sopandi (EDUSAINS, 2020)
DEVELOPMENT OF TEACHING MATERIALS BASED ON CONCEPTUAL CHANGE TEXT ON REDOX MATERIALS FOR BASIC CHEMICALS ON REDOX CONCEPTAbstractThe problem in this study is that there are still many students who have difficulty learning basic chemical concepts and experience misconceptions. One way to overcome student difficulties in understanding the concept of chemistry is to provide quality learning media. This study aims to produce learning media in the form of quality teaching materials. The teaching materials developed are chemical teaching materials based on Conceptual Change Text (CCT). The research data were obtained from the results of validation of teaching materials from experts and the results of a questionnaire distributed to 30 students. This research was conducted using the R&D method with the research subjects being teaching materials and students. Based on the data generated in this study, it was found that the development of CCT-based teaching materials when viewed from the aspects of content feasibility, presentation feasibility, language assessment, multiple chemical representations assessed by some experts, it can be concluded that the teaching materials developed are good and suitable for use in the field with some improvements with an average validation value of 4. Besides, a limited test was also carried out on students of the teaching materials that were being developed and students responded well to the teaching materials because it could help them understand the average value of 85. AbstrakPermasalahan dalam penelitian ini adalah masih banyaknya mahasiswa yang mengalami kesulitan dalam belajar konsep kimia dasar dan mengalami miskonsepsi. Salah satu cara untuk mengatasi kesulitan mahasiswa dalam memahami konsep kimia adalah menyediakan media pembelajaran yang berkualitas. Penelitian ini bertujuan untuk menghasilkan media pembelajaran berupa bahan ajar yang berkualitas. Bahan ajar dikembangkan adalah bahan ajar kimia berbasis Conceptual Change Text (CCT). Data penelitian diperoleh dari hasil validasi bahan ajar dari para ahli dan hasil angket yang disebarkan kepada 30 orang mahasiswa.  Penelitian ini dilakukan dengan metode R&D dengan subjek penelitian adalah bahan ajar dan mahasiswa. Berdasarkan data yang dihasilkan dalam penelitian ini diperoleh hasil bahwa pengembangan bahan ajar berbasis CCT jika dilihat dari aspek kelayakan isi, kelayakan penyajian, penilaian bahasa, penilaian multiple representasi kimia yang dinilai oleh beberapa ahli dapat disimpulkan bahwa bahan ajar yang dikembangkan sudah baik dan layak digunakan di lapangan dengan beberapa perbaikan dengan rata-rata nilai validasi 4. Selain itu juga dilakukan uji terbatas terhadap mahasiswa terhadap bahan ajar yang sedang dikembangkan dan mahasiswa merespon dengan baik bahan ajar tersebut karena bisa membantu mereka dalam memahami dengan rata-rata nilai 85. konsep.